2013
DOI: 10.1111/tri.12138
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute renal injury in living donor liver transplantation: evaluation of the RIFLE criteria

Abstract: Summary Acute renal injury (ARI) is a serious complication after liver transplantation. This study investigated the usefulness of the RIFLE criteria in living donor liver transplantation (LDLT) and the prognostic impact of ARI after LDLT. We analyzed 200 consecutive adult LDLT patients, categorized as risk (R), injury (I), or failure (F), according to the RIFLE criteria. ARI occurred in 60.5% of patients: R‐class, 23.5%; I‐class, 21%; and F‐class, 16%. Four patients in Group‐A (normal renal function and R‐clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
100
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 63 publications
15
100
3
Order By: Relevance
“…Therefore, we used the RIFLE criteria to define AKI after LDLT. We reported previously that the RIFLE criteria offer a useful predictive tool after LDLT [22]. The risk factors for AKI identified in the present study included MELD score of ≥20, graft weight per recipient body weight ratio of <0.7%, blood loss/body weight ratio of >55 mL/kg, no use of MMF, and the presence of preoperative diabetes mellitus [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we used the RIFLE criteria to define AKI after LDLT. We reported previously that the RIFLE criteria offer a useful predictive tool after LDLT [22]. The risk factors for AKI identified in the present study included MELD score of ≥20, graft weight per recipient body weight ratio of <0.7%, blood loss/body weight ratio of >55 mL/kg, no use of MMF, and the presence of preoperative diabetes mellitus [22].…”
Section: Discussionmentioning
confidence: 99%
“…We reported previously that the RIFLE criteria offer a useful predictive tool after LDLT [22]. The risk factors for AKI identified in the present study included MELD score of ≥20, graft weight per recipient body weight ratio of <0.7%, blood loss/body weight ratio of >55 mL/kg, no use of MMF, and the presence of preoperative diabetes mellitus [22]. For a recipient with these risk factors to progress to severe AKI, a systematic operative plan and postoperative care should be considered, which include sufficient graft volume, use of MMF combined with reduced CNI, transfusion during the perioperative phase, and early introduction of renal replacement therapy to prevent severe AKI [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study from Ireland by O'Riordan et al [29] found that 10 y cumulative incidence of renal dysfunction for stages 0/1, 2, 3, 4 and 5 of CKD as 9.61, 53.7, 56.77, 6.11 and 2.62%, respectively. The incidence of AKI was 60.5% at an average tacrolimus trough level of 10.3±0.51 (µg/l) in a study conducted by Utsumi et al [30] from Japan. The lower incidence of renal dysfunction in our study may be due to the relatively low trough levels (<7 µg/l) of tacrolimus maintained for our patients.…”
Section: Resultsmentioning
confidence: 99%